Informe final de práctica realizada en la granja infantil “Jesús de la Buena Esperanza” (2011)
This practice plan was carried out at the Farm Infant Jesus of Good Hope, with vulnerable population. This practice takes place mainly in two areas: individual clinical intervention and psychoeducational intervention. On the first axis, will be from a psychoanalytic orientation, which allows the rescue by the peculiarity of the subject, characteristic of this clinic is not in principle treat the symptom of the subject, but it is necessary to build a space for what is subjective, where children and young people achieve order something of its history, being questioned about his position "and thus begin to rebuild some of its particular history. With regard to psycho-educational intervention spaces are developed oriented notions of sexuality, life projects and workshops of psychoactive substances in order to prevent and promote best practice on issues that require social demand as much of the population has had direct contact with this type of practice.